Chondromyxoid Fibroma of The Lumbar Spine: Case Report and Review of The Literature - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2012)
Chondromyxoid fibroma originating from axial skeleton is a very rare benign bone neoplasm. There are a few reported lumbar cases in the literature and it can be pre-operatively misdiagnosed as other tumors of spine. A 20-year-old girl presented to our outpatient clinic with right hip and leg pain of 3 months' duration. Physical and neurological examinations were unremarkable and laboratory test results were within normal limits. Imaging studies revealed a cystic lesion in the right half of the L5 vertebra and extending to the posterior elements of the vertebra. CT-guided biopsy result was inconclusive. Surgery was planned. Digital subtraction angiography and embolization were carried out preoperatively. During surgery, L5 laminectomy and curettage of the lesion were performed, taking care to leave the cortex intact. Bilateral L4, S1, and left L5 transpedicular instrumentation and right L5 vertebroplasty were also carried out. The operation relieved the patient's pain. The paper discusses the clinical, histological, and radiological characteristics of chondromyxoid fibroma, as well as differential diagnosis and treatment modalities.
Keywords: Chondromyxoid fibroma; Lumbar spine; Bone tumor; Curettage; Instrumentation; THORACIC SPINE; CERVICAL-SPINE; CORD COMPRESSION; BONE